The Correlation Between Balance And Lower Limb Power With The Speed Of Naeryo Chagi Kick In Taekwondo - Wilda Destriananingrum; Marta Dinata; Suwarli; Frans Nurseto (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to determine the relationship between balance and leg muscle power to Naeryo Chagi's kick speed in Taekwondo Club Nawesena athletes in Bandar Lampung City. The research method used a correlational approach with a sample of 30 athletes. The instruments used included a balance test with a standing stroke test, leg muscle power with a vertical jump, and Naeryo Chagi's kick speed with a stopwatch for 15 seconds. The results showed that there was a significant relationship between balance and Naeryo Chagi's kick speed (r count = 0.441 > r table = 0.374) and between leg muscle power and Naeryo Chagi's kick speed (r count = 0.525 > r table = 0.374). Simultaneously, balance and leg muscle power were also significantly related to Naeryo Chagi's kick speed (r count = 0.687 > r table = 0.374) with a contribution of 47.19%.